2013
DOI: 10.1111/2049-632x.12061
|View full text |Cite
|
Sign up to set email alerts
|

Role ofBordetella pertussisRseA in the cell envelope stress response and adenylate cyclase toxin release

Abstract: Bordetella pertussis is the bacterial agent of the human disease, whooping cough. In many bacteria, the extracellular function sigma factor σE is central to the response to envelope stress, and its activity is negatively controlled by the RseA anti-sigma factor. In this study, the role of RseA in B. pertussis envelope stress responses was investigated. Compared with the wild-type strain, an rseA mutant showed elevated resistance to envelope stress and enhanced growth at 25°C. rpoH and other predicted σE target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 59 publications
2
19
0
Order By: Relevance
“…Protein samples used for SDS-PAGE analysis were prepared as described previously, with some modifications (23). Briefly, proteins in the culture fluids were precipitated with 15% trichloroacetic acid after removing bacterial cells by centrifugation at 7,500 rpm at 4°C for 10 min and passing through a 0.45-m-pore-size membrane filter.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Protein samples used for SDS-PAGE analysis were prepared as described previously, with some modifications (23). Briefly, proteins in the culture fluids were precipitated with 15% trichloroacetic acid after removing bacterial cells by centrifugation at 7,500 rpm at 4°C for 10 min and passing through a 0.45-m-pore-size membrane filter.…”
Section: Methodsmentioning
confidence: 99%
“…Proteins separated by SDS-PAGE were transferred to a polyvinylidene difluoride (PVDF) membrane and reacted with diluted antibodies at room temperature for 1 h. Unless described elsewhere, dilution ratios were 1,500-fold for antipertactin (anti-Prn) (24), anti-pertussis toxin (anti-PTX) (Santa Cruz Biotechnology, Inc.), and anti-adenylate cyclase toxin (anti-ACT) (Santa Cruz Biotechnology, Inc.) antibodies from mouse and anti-Bsp22 (kind gift from Akio Abe, Kitasato University) and anti-filamentous hemagglutinin (anti-FHA) antibodies from rabbit (23). Rabbit anti-BspR antibody (kind gift from Akio Abe, Kitasato University) was diluted 800-fold.…”
Section: Methodsmentioning
confidence: 99%
“…In Bordetella bronchiseptica, Sig E has been shown to facilitate survival of membrane perturbations and is required for virulence in immunocompromised mice (12). It has also been shown that in B. pertussis RpoE influences alleviation of membrane stress (13). RpoE is controlled by an anti-sigma factor known as RseA.…”
mentioning
confidence: 99%
“…RseA sequesters RpoE to the inner membrane, which renders it transcriptionally inactive; however, proteolytic cleavage of RseA or genetic mutation to rseA results in transcriptional activation of RpoE. Deletion of rseA from B. pertussis strain UT25 resulted in an increased amount and diversity of periplasmic proteins (13). Surprisingly, it was shown that the rseA gene deletion mutant (PM18) of the B. pertussis strain UT25 also released a large amount of adenylate cyclase toxin (ACT) into the culture media (13).…”
mentioning
confidence: 99%
See 1 more Smart Citation